Pengaruh Rasio RGEC, Bank Size, Market Value, serta Variabel Makroekonomi terhadap Prediksi Financial Distress Menggunakan CD-Index - Wanda Hamidatun Nisak (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
The Bank is a financial institution that functions to accumulate and distribute funds to the public and providing other banking services. In channelling funds, banks are not protected from the internal and external risks that cause financial difficulties. This study examines the influence of RGEC factors, bank size, market value, and macroeconomic to predict financial distress using the Crisis and Default Index. RGEC factors used in this study is risk profile which is proxy by NPL and LDR, good corporate governance is proxy of the size of board directors, earnings proxied by ROA, ROE, NIM, BOPO, and capital is proxied by CAR. The variable of bank size and market value is proxied by PBV and PER. While the macroeconomic variables used are economic growth, inflation, and exchange rates. This study used 19 banks in the BUSN group as a research sample during 2015-2019. The result showed that internal factors and bank size did not significantly influence the prediction of financial distress. Market value variable proxied by PBV has a significant negative effect on the prediction of financial distress. This is important for internal bank parties to keep stock prices from falling and investors are interested in investing; PER and macroeconomic variables do not significantly affect the prediction of financial distress because good internal banking fundamentals face changes in economic conditions. There is no influence of variables with financial distress because these variables appropriate with Bank Indonesia and BUSN are implementing them correctly.